Intense Pericardial Involvement in Polycystic Echinococcosis Submitted to Successful Medical Treatment - Mariani Madisson-Bernardo; Daniel J. Bernardo; Henrique Simão Trad; U G Meneghelli; Márcia G. Villanova; André Schmidt (2019)
A 49-year-old man, from the state of Tocantins (northern Brazil) was initially seen in 2006 and diagnosed as polycystic echinococcosis with liver and lungs involvement.He was initially treated with medical therapy but a right lobectomy in 2008 and cholescistectomy and partial hepatectomy were performed in 2009.He returned to his hometown and had annual clinical follow ups and remained stable.In May 2013, the patient complained of dyspnea on minimal exertion and atypical chest pain.At admission, an ECG evidenced sinus tachycardia and diffuse changes in ventricular repolarization (Figure 1).A magnetic resonance imaging of the thorax demonstrated pericardial multicystic formation compatible with polycystic hydatid disease in the pericardium and pulmonary cysts (Figure 2).An echocardiogram revealed pericardial thickening without signs of increased intracavitary pressure and preserved systolic performance (LVEF=78%).A medical conference decided that surgery was not indicated due to the risk of spreading the disease to adjacent organs and to the widespread distribution of the lesions (some cysts were crossing the diaphragm).Medical treatment was initiated with albendazole in high doses (15 mg/kg/ day).Gradually, his symptoms improved.Cardiac magnetic resonance imaging was repeated 16 days later to better evaluate cardiac involvement and a significant reduction of hydatid cysts was noted (Figure 3; Movie in the Data Supplement).He was discharged and oriented to maintain continuous albendazole treatment.A year later, he was clinically asymptomatic and with no cardiac involvement detected in a control thoracic computed tomography.